1993
DOI: 10.1021/bi00070a023
|View full text |Cite
|
Sign up to set email alerts
|

Serine92 (F7) contributes to the control of heme reactivity and stability in myoglobin

Abstract: The effects of mutation of the conserved serine92 residue to alanine, valine, and leucine in pig myoglobin have been determined. In myoglobin crystal structures, the hydroxyl group of serine92 is within hydrogen-bonding distance of the N delta-H of histidine93, whose N epsilon coordinates the iron atom of the heme prosthetic group. The association equilibrium constants of the ferrous forms of the mutant myoglobins for O2, CO, and methyl and ethyl isocyanide are increased 1.3-13-fold relative to the wild-type p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
84
1

Year Published

1996
1996
2009
2009

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 85 publications
(94 citation statements)
references
References 26 publications
9
84
1
Order By: Relevance
“…The strength of the hydrogen bond formed by a nitrogen proton in the proximal histidine and the polarity of the environment are powerful factors for determining the Fe-His stretching frequency in the heme-histidine moiety. This hydrogen bonding network in hemoglobins and myoglobins has also been also related to ligand affinity (37,40). The significant differences observed in the heme-ligand dissociation rate constants between Mb and Hb Asc have mainly been attributed to the tilted orientation of the His(F8) with regard to the pyrrole rings of the heme (45).…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…The strength of the hydrogen bond formed by a nitrogen proton in the proximal histidine and the polarity of the environment are powerful factors for determining the Fe-His stretching frequency in the heme-histidine moiety. This hydrogen bonding network in hemoglobins and myoglobins has also been also related to ligand affinity (37,40). The significant differences observed in the heme-ligand dissociation rate constants between Mb and Hb Asc have mainly been attributed to the tilted orientation of the His(F8) with regard to the pyrrole rings of the heme (45).…”
Section: Discussionmentioning
confidence: 94%
“…3). This last pair of amino acids has been proposed to stabilize the oxygenated form of HbII LP by means of strong and weak hydrogen bonds, respectively (37,40). Hb Asc also has a Tyr(B10) and a Gln(E7), and a high oxygen affinity and unusually slow off rate for oxygen dissociation (15,41).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Smerdon and co-workers have measured a small difference in CO recombination kinetics in the pig myoglobin mutant S92A, where the hydrogen bond between the proximal histidine and Ser 92 is removed (Smerdon et al, 1993), though the changes are smaller than those observed by replacement of 4-MeIm with N-MeIm in H93G. This might be because the histidine in wild type myoglobin hydrogen bonds with both Ser 92 and the backbone carbonyl of Leu 89 (Cheng & Shoenborn, 1991).…”
Section: Mechanism Of Ligand Exchange In H93g(l)comentioning
confidence: 99%